(untitled) (Journal of Bangladesh Academy of Sciences, 2022)
Bloodstream infections (BSI) are serious, life-threatening, and critical clinical conditions with high global human morbidity and mortality rates. This study aimed to determine the Gram-negative bacterial profiles and antimicrobial resistance patterns of acute bloodstream infections in rural patients. Three hundred forty-six blood samples were collected and analyzed with the BD BactecTM FX40 automated culture system, selective media culture, and biochemical parameters. Finally, antimicrobial susceptibility testing was performed using the disk diffusion method. The most common age group affected out of 51 cases was 41-60 years, with 20 patients (39.22%), and 1-15 years, with 2 patients (3.92%). Male patients were more susceptible (66.67%) than female patients. Among the isolates, E. coli was the most common, with 23 cases (45.1%); Cephradine was the most resistant antibiotic, and Imipenem was the most sensitive. Multiple drug-resistant pathogens were one of the most notable findings in our work. Our study will surely provide the best guide for properly treating antibacterial-resistant bacterial diseases and minimizing their critical mortality and morbidity. J. Bangladesh Acad. Sci. 46(2); 185-191: December 2022